(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Congenital Rubella Syndrome is caused by the destructive action of the rubella virus on the fetus at a critical time in development. If the infection occurs at 0-12 weeks of conception, there is a 51% chance of effect on the infant. Along with eye problems, mental retardation, deafness, growth retardation and developmental delays, some patient who survive infection, takes birth with congenital heart disease. Patent ductus arteriosus (PDA) is the most commonly reported heart problem. Case Report: Two cases of congenital rubella syndrome with large patent ductus arteriosus and severe pulmonary hypertension are reported here, whose PDA’s were closed with Lifetech PDA occluder devices. One of them had multiple peripheral pulmonary stenosis which were also dilated with balloons. Both of them had interventions in same day. Key words: Patent ductus arteriosus (PDA); congenital rubella syndrome; severe pulmonary hypertension DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8627 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 43-45